Cerebral vascular malformations: Time-resolved CT angiography compared to DSA - Shankar, Jai Jai Shiva (Neuroradiol J, 2015)
PURPOSE: The purpose of this article is to prospectively test the hypothesis that time-resolved CT angiography (TRCTA) on a Toshiba 320-slice CT scanner enables the same characterization of cerebral vascular malformation (CVM) including arteriovenous malformation (AVM), dural arteriovenous fistula (DAVF), pial arteriovenous fistula (PAVF) and developmental venous anomaly (DVA) compared to digital subtraction angiography (DSA). MATERIALS AND METHODS: Eighteen (eight males, 10 females) consecutive patients (11 AVM, four DAVF, one PAVF, and two DVA) underwent 19 TRCTA (Aquillion one, Toshiba) for suspected CVM diagnosed on routine CT or MRI. One patient with a dural AVF underwent TRCTA and DSA twice before and after treatment. Of the 18 patients, 13 were followed with DSA (Artis, Siemens) within two months of TRCTA. Twenty-three sequential volume acquisitions of the whole head were acquired after injection of 50 ml contrast at the rate of 4 ml/sec. Two patients with DVA did not undergo DSA. Two TRCTA were not assessed because of technical problems. TRCTAs were independently reviewed by two neuroradiologists and DSA by two other neuroradiologists and graded according to the Spetzler-Martin classification, Borden classification, overall diagnostic quality, and level of confidence. Weighted kappa coefficients (k) were calculated to compare reader’s assessment of DSA vs TRCTA. RESULTS: There was excellent (k = 0.83 and 1) to good (k = 0.56, 0.61, 0.65 and 0.67) agreement between the different possible pairs of neuroradiologists for the assessment of vascular malformations. CONCLUSION: TRCTA may be a sufficient noninvasive substitute for conventional DSA in certain clinical situations.